Effect of process-dependent parameters of the handling-and-storage facility operation on the cargo handling cost - Шраменко, Наталя Юріївна (Eastern-European Journal of Enterprise Technologies, 2015)
Analysis of the handling-and-storage facility operation revealed the disadvantages of the technology that is related to the non-consideration of incoming cargo traffic variations in the planning and organization of industrial activity. The criterion of the handling-and-storage facility operation that presents unit costs for cargo handling has been formalized. The criterion makes it possible to take into account the cargo owner’s costs associated with downtime of vehicles waiting for service and the storage facility costs related to the maintenance of productive resources. The regression analysis results have demonstrated that a number of loading and unloading mechanisms were of the greatest effect on the cargo handling cost at the handling-and-storage facility. The results obtained determine the formation of the rational service technology of cargo transportation at the handling-and-storage facility due to the choice of the rational number of loading and unloading mechanisms, depending on the volume of incoming cargo traffic.